Pengembangan Potensi Sumber Daya Manusia dengan Inovasi Pengemasan Produk UMKM Terasi Udang Empang, Baso Ikan dan Kerupuk Ikan di Kecamatan Pedes Karawang - July Yuliawati; Sari Marliani; Ery Rosmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine and analyze the development of human resource potential with innovation in packaging of shrimp paste, fish balls and fish crackers in Pedes District, Karawang Regency. The method used is descriptive qualitative with the type of research, interviews, field observations.The results of the study are that the potential of human resources in Pedes District is quite good, only not well developed, proven by lack of insight and lack of creativity such as developing new innovations in product packaging, promotion, sales using social media.The potential of UMKM Actors of Shrimp Paste, Fish Balls and Fish Crackers is quite good, only lacking guidance from the village or from the sub-district such as training from the industry office. With innovation in shrimp paste packaging from woven bamboo products on UMKM products, it adds creativity and preservation of traditional weaving. While for the innovative packaging of fish balls and fish crackers, plastic pouches are used which are labeled with the UMKM name. MSME actors must receive continuous coaching or training that can later become a role model for other MSMEs to continue to develop and become superior in Pedes District.